2011
DOI: 10.1007/s13105-011-0130-2
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamtannin B-1, a natural antioxidant that reduces the effects of H2O2 on CCK-8-evoked responses in mouse pancreatic acinar cells

Abstract: This work was designed in order to gain an insight on the mechanisms by which antioxidants prevent pancreatic disorders. We have examined the properties of cinnamtannin B-1, which belongs to the class of polyphenols, against the effect of hydrogen peroxide (H(2)O(2)) in mouse pancreatic acinar cells. We have studied Ca(2+) mobilization, oxidative state, amylase secretion, and cell viability of cells treated with cinnamtannin B-1 in the presence of various concentrations of H(2)O(2). We found that H(2)O(2) (0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Alternatively, ROS have been shown to both stimulate amylase release in mouse pancreatic acinar cells [37] as well as cause inhibition of CCK-stimulated amylase release in vitro [38] , [39] . At low doses, PFOA-mediated ROS production may thus act to stimulate enzyme secretion while at a higher dose (5.0 mg/kg BW/day) PFOA-stimulated ROS production may inhibit secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, ROS have been shown to both stimulate amylase release in mouse pancreatic acinar cells [37] as well as cause inhibition of CCK-stimulated amylase release in vitro [38] , [39] . At low doses, PFOA-mediated ROS production may thus act to stimulate enzyme secretion while at a higher dose (5.0 mg/kg BW/day) PFOA-stimulated ROS production may inhibit secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ROS accumulation was measured using 2′,7′-dichlorofluorescein diacetate (DCFDA, Sigma-Aldrich) fluorescent dye [ 17 ]. Cells were washed twice with PBS; thereafter, 50 μ l of DCFDA solution (5 μ M in PBS) was added for each well and incubated for 30 minutes in cell culture incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have reported that cinnamtannin B-1 reduces endogenous ROS production stimulated by thrombin, modulates Ca 2+ mobilization in human platelets, 21 and significantly reduces the oxidant action of H 2 O 2 by the decrease in the oxidation of the redox sensitive dye CM-H 2 DCFDA on CCK-8-evoked responses in mouse pancreatic acinar cells. 22 In addition, our previous study have determined that cinnamatannin B-1 (10) is a major compound of O. japonica.…”
Section: Resultsmentioning
confidence: 99%